2018
DOI: 10.1021/acs.jmedchem.7b01820
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Alcoholic Steatosis in Mice with a Peripherally Restricted Purine Antagonist of the Type 1 Cannabinoid Receptor

Abstract: Type 1 cannabinoid receptor (CB1) antagonists have demonstrated promise for the treatment of obesity, liver disease, metabolic syndrome, and dyslipidemias. However, the inhibition of CB1 receptors in the central nervous system can produce adverse effects, including depression, anxiety, and suicidal ideation. Efforts are now underway to produce peripherally restricted CB1 antagonists to circumvent CNS-associated undesirable effects. In this study, a series of analogues were explored in which the 4-aminopiperidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…Research has shown that CB1-deficient mice are resistant to alcoholic liver [149], and the pro-inflammatory response caused by CB1 can be negatively regulated by CB2 [150]. Moreover, it has shown that CB1 antagonists and CB2 agonists can protect alcohol-induced liver injury through different pathways [151,152]. However, the usage of CB1 antagonists has been limited in the treatment of liver diseases due to its neuropsychiatric side effects.…”
Section: Current Therapiesmentioning
confidence: 99%
“…Research has shown that CB1-deficient mice are resistant to alcoholic liver [149], and the pro-inflammatory response caused by CB1 can be negatively regulated by CB2 [150]. Moreover, it has shown that CB1 antagonists and CB2 agonists can protect alcohol-induced liver injury through different pathways [151,152]. However, the usage of CB1 antagonists has been limited in the treatment of liver diseases due to its neuropsychiatric side effects.…”
Section: Current Therapiesmentioning
confidence: 99%
“…In addition to metabolic disorders, preclinical research suggests peripherally restricted antagonists have beneficial effects on kidney diseases [92,93], liver fibrosis and steatosis [94][95][96], pulmonary fibrosis [97,98], and alcoholism [99] (see Table 2). In some cases, some third-generation compounds have been designed to inhibit more than one molecular target.…”
Section: Peripherally Restricted Cb 1 Antagonistsmentioning
confidence: 99%
“…Recently, a chemical compound that acts as a peripherally restricted antagonist of CB1R has been developed, which showed negligible CNS penetration and remarkable attenuation of alcoholic steatosis in mice. 42 Thus, there is a silver lining in the possibility that with refinement and adjustment, this chemical might be a profound lead compound that could undergo clinical trials as a novel therapeutic target. In short, a growing number of experimental findings on the involvement of hepatic endocannabinoids in the pathophysiology of ALD has enabled the development of endocannabinoid-based or cannabinoid receptor–based pharmacological approaches that, it is hoped, could become a novel therapeutic strategy for ALD.…”
Section: Therapeutic Implications For Aldmentioning
confidence: 99%